Directive competence and school management in the EI CET 34. Chancay. Lima - More Herrera , Lesly Karol Lucia (2024)
One of the main problems for the achievement of student learning is the lack of adequate management in the management of school management and it is the absence of competencies in those who direct the educational institutions are responsible for this lack of management. . Therefore, the objective of this research is to identify and establish the relationship between managerial competencies and school management in the IE CET 34 of Chancay. A quantitative approach is used with a hypothetical method, cross-sectional and ordinal level. A descriptive correlational design shapes this study in 78 teachers. Two data collection instruments validated by three expert juries and the measurement of a reliability index using Cronbach's Alpha guarantee suitability in the study. To analyze the data, we used descriptive statistics and Spearnan's Rho Coefficient to test hypotheses. The results showed a notable relationship between the managerial competencies in the school management of the institution in question.